Space and storage requirements for effective clothing instruction - Farrales, Gloria Cachuela 1920- (1966)
This is an investigation of the factors that must be considered in planning space and storage facilities for a clothing laboratory, how different articles and pieces of furniture should be arranged to attain the goals of home economics education, and the things to be done to improve the present clothing laboratory facilities.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Dressmaking -- Study and teaching